2012
DOI: 10.3390/v4112417
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Functions of a Prophage Recombination Directionality Factor

Abstract: Recombination directionality factors (RDFs), or excisionases, are essential players of prophage excisive recombination. Despite the essentially catalytic role of the integrase in both integrative and excisive recombination, RDFs are required to direct the reaction towards excision and to prevent re-integration of the prophage genome when entering a lytic cycle. KplE1, HK620 and numerous (pro)phages that integrate at the same site in enterobacteria genomes (such as the argW tRNA gene) all share a highly conserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Interestingly, the full-length Euo protein appears to harbour TorI-like wHTHs arranged in tandem, the first from residues 6–62 and the second from residues 78–137, suggesting that an Euo dimer can bind multiple minimal Euo boxes and that this tandem arrangement of putative wHTH promotes the formation of a stable nucleoprotein complex at chlamydial promoters, potentially accounting for the binding to the multiple minimal Euo boxes described above. We mutated the conserved arginine and tyrosine residues (individually and in combination) in the Euo wHTH that are required for DNA binding of TorI ( Panis et al , 2012 ) and found that the triple mutation (Y31A/R47A/Y100A) impaired binding of Euo on the P queF promoter fused to the lacZ gene, in the E. coli transcription interference assay ( Figure 7b ). Thus, binding of Euo resembles that of TorI-like excisionases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the full-length Euo protein appears to harbour TorI-like wHTHs arranged in tandem, the first from residues 6–62 and the second from residues 78–137, suggesting that an Euo dimer can bind multiple minimal Euo boxes and that this tandem arrangement of putative wHTH promotes the formation of a stable nucleoprotein complex at chlamydial promoters, potentially accounting for the binding to the multiple minimal Euo boxes described above. We mutated the conserved arginine and tyrosine residues (individually and in combination) in the Euo wHTH that are required for DNA binding of TorI ( Panis et al , 2012 ) and found that the triple mutation (Y31A/R47A/Y100A) impaired binding of Euo on the P queF promoter fused to the lacZ gene, in the E. coli transcription interference assay ( Figure 7b ). Thus, binding of Euo resembles that of TorI-like excisionases.…”
Section: Resultsmentioning
confidence: 99%
“…Speculating on the mode of binding of Euo to DNA via TorI-like wHTHs, it is noteworthy that multiple TorI binding sites are thought to have a crucial role in (i) bending DNA (nucleoprotein filament) and (ii) positioning recombination integrase proteins for proper formation of the excisive nucleoprotein complex ( Panis et al , 2010a , b , 2012 ). Thus, these Euo boxes could also serve in proper positioning of RNAP for open complex formation in transcription initiation.…”
Section: Discussionmentioning
confidence: 99%
“…None of the 35 identified ORFs yielded any similarity to previously described excisionases. However, when the vpiT (VC0817) amino acid sequence was submitted to HHpred, 52 amino acids near the N terminus displayed a distant relationship to TorI, a previously characterized excisionase (25,31,52). Although the shared identity in this region was 12%, with an E value of 0.0061, the predicted secondary elements of these regions were nearly identical (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, the small TorI protein encoded by the defective KplE1 prophage in Escherichia coli K12 was previously shown to downregulate the host torCAD operon, which is involved in the anaerobic respiration of trimethylamine N-oxide (TMAO) and is controlled by the two component system TorS/TorR 33 . More specifically, although TorI is essentially a recombination directionality factor, 34 it is also able to bind the TorR response regulator at its effector site, possibly preventing RNA-polymerase recruitment to the torCAD operon 33 . A related example concerns the secondary activity of the CI repressor from phage λ and several other phages, including P22.…”
Section: The Increasing Intricacy Of Phage–host Interactionsmentioning
confidence: 99%